2019
DOI: 10.21203/rs.2.12740/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with utilization of maternal health services by female sex workers in Uganda: a Health facility-based survey

Abstract: Introduction Female sex workers (FSWs) are marginalized due to social rejection and stigma, especially in countries where the practice is illegal. Many FSWs are mothers but little is known about their utilization of maternal services. This study investigated the determinants of utilization of maternal services by FSWs in Uganda. Methods FSWs were recruited from the “Most at-Risk Initiative” clinics in Uganda. We analyzed data for 318 FSWs who had given birth within two years of the study to estimate the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This is much higher than the 3% of all women aged 15-49 in Guinea-Bissau who did not receive antenatal care [51]. Destigmatizing and making antenatal care services friendly toward adolescents who sell sex may improve uptake among this population [52].…”
Section: Discussionmentioning
confidence: 99%
“…This is much higher than the 3% of all women aged 15-49 in Guinea-Bissau who did not receive antenatal care [51]. Destigmatizing and making antenatal care services friendly toward adolescents who sell sex may improve uptake among this population [52].…”
Section: Discussionmentioning
confidence: 99%
“…Destigmatizing and making antenatal care services friendly toward FSW and adolescents may improve uptake among these populations. [24] Over half of FSW in this study who started selling sex while underage reported current use of male condoms for contraception, which can also help protect them from HIV and other STIs. However, over one third had experienced STI symptoms in the past 12 months, suggesting the need for further prevention and treatment services.…”
Section: Discussionmentioning
confidence: 86%
“…Destigmatizing and making antenatal care services friendly toward FSW and adolescents may improve uptake among these populations. [24]…”
Section: Discussionmentioning
confidence: 99%
“…However, the continuum of care is often narrowed to concentrate on antenatal, delivery and postnatal care provided by skilled healthcare workers [11]. Although it is accepted that each element of care will improve outcomes, an integrated approach has been shown to be the most effective [10,12,13], and utilisation of the continuum of care is recognised as an important means of reducing maternal and neonatal mortality rates [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have highlighted the importance of maternal healthcare [2][3][4][5][6][7][8][9] and identified some of the factors that influence the individual utilisation of antenatal care, delivery care and postnatal care [23][24][25][26][27][28][29][30][31], very few studies have investigated the continuum of care. Given the importance of the integrated use of maternal healthcare, it is vital that the barriers preventing women accessing the continuum are understood [10,[12][13][14][15]. This information is key for policy makers to be able to design and implement effective strategies to increase utilisation of maternal healthcare across the continuum.…”
Section: Introductionmentioning
confidence: 99%